Algebraic multigrid methods for magnetostatic field problems - Reitzinger, S.; Kaltenbacher, M. (IEEE transactions on magnetics, 2002)
The finite-element (FE) method, which will be used for the discretization of three-dimensional magnetostatic field problems, usually yields a large and sparse matrix equation. For different FE-discretizations (i.e., Lagrange and Nedelec FE-functions) we will present appropriate algebraic multigrid solvers (preconditioners) for the efficient solution of the arising system of equations. Numerical results will demonstrate the applicability of the developed algebraic multigrid methods.